Implementasi Metode Multifactor Evaluation Process Pemilihan Guru Terbaik Pada SMP Darul Ulum Waru Berbasis Web - Kapindho Febriyanto; Muhammad Fatkhur Rizal; Chamdan Mashuri; Didiek Rusdyanto (Jurnal Penelitian Teknologi Informasi dan Sains, 2025)
The decision support system for determining the best teachers at SMP Darul Ulum Waru aims to facilitate the selection and assessment of teacher performance. Currently, the selection of the best teachers still involves negotiations or discussions and has not yet been systematic in determining the best teachers. this process results in outcomes that appear subjective, as teacher evaluations are conducted every year in the even semester to boost the work spirit of each teacher in educating their students and to reward them for their achieved performance. To improve efficiency and accuracy, a system for selecting the best teachers is needed using the MFEP (Multifactor Evaluation Process) method, which is more flexible in determining the weight of criteria. In this method, more prioritized criteria receive greater weight and are easier to apply, making data processing faster. In the MFEP process, calculations are made using predetermined criteria, including politeness, work accuracy, orderliness, compliance, and work enthusiasm. Calculations will be conducted for each teacher based on the specified criteria and weighting, which will ultimately result in recommendations for the best teachers.In the MFEP system, the selection of the best teachers that has been created was tested 20 times manually with an accuracy of 85.88%.